A systematic review of psychological difficulties among elite sports coaches - Kang, Sangwook; Lee, Seungjoo (Frontiers in Psychology, 2025)
IntroductionThis systematic review examined the psychological difficulties experienced by elite sports coaches, focusing on their causes, consequences, and potential interventions. Despite increasing recognition of the challenges faced by coaches, limited attention has been paid to understanding their psychological difficulties and available support systems.MethodsFollowing PRISMA guidelines, a comprehensive search was conducted across PubMed, Scopus, Web of Science, and SPORTDiscus. A total of 101 peer-reviewed studies published between 2010 and 2024 were identified and analyzed. Keywords such as “psychological difficulties," “stress," “burnout," and “coach-athlete relationship" were used to guide the search strategy.ResultsFindings revealed that elite coaches frequently encounter psychological difficulties stemming from performance pressure, excessive workloads, the complexities of athlete management, and external social expectations. These stressors were associated with heightened risk of burnout, diminished psychological wellbeing, reduced coaching effectiveness, and strained coach-athlete relationships.DiscussionDespite the prevalence and severity of these psychological difficulties, relatively few studies have addressed intervention strategies specifically targeting coaches. This review highlights the urgent need for evidence-based support systems to help coaches manage psychological difficulties and optimize their professional functioning. The findings provide valuable insights to inform future research and practical initiatives aimed at creating a healthier and more sustainable environment for both coaches and athletes in elite sports settings.